...3 terms to evaluate: (3-6)x + (4-6)x + (5-6)x = 72. Simply the

**LHS**. What does it give? [ = -6x ] Then, solving for x ...2 Answers · Science & Mathematics · 11/11/2020

Yep, ordinary algebra. Divide both sides by the same value and the equation remains balanced. The

**LHS**still = the RHS. So divide away and enjoy.3 Answers · Science & Mathematics · 19/08/2020

RHS = cot²(x)[csc³(x) - csc(x)] = cot²(x)csc(x)[csc²(x) - 1] = cot²(x)csc(x)cot²(x) = cot⁴(x)csc(x) =

**LHS**1 Answers · Science & Mathematics · 09/05/2020

x^2 = y ... y is a variable, not a constant like 4 ... different rules apply a^y = b^x a = b^(x/y) until you know a number value for b and y (which has become a root) we don 't know if the answer is pos, neg, or imaginary.

2 Answers · Education & Reference · 30/03/2020

... + Fr = mh''. Use the correct signs for the

**LHS**terms. Fg is a constant [which one?]. Note that h'...1 Answers · Science & Mathematics · 28/02/2020

**LHS**= xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x**LHS**= RHS1 Answers · Science & Mathematics · 03/08/2019

...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while

**LHS**is irrational. This is a contradiction. Hence the sum must...4 Answers · Science & Mathematics · 03/08/2019

... / R GmM / R = 2*KE and you should recognize the

**LHS**as being equal to -GPE. If you find this helpful, please award...1 Answers · Science & Mathematics · 07/05/2019

... the given P(t) and showing that it equals the

**LHS**. Or you can find the solution by solving the DE this way: ...1 Answers · Science & Mathematics · 14/02/2019

....N. (oxidation number) of H on the

**LHS**= O.N. of H on the RHS = +1...⁻ O.N. of H on the**LHS**= O.N. of H on the RHS, as...3 Answers · Science & Mathematics · 16/02/2019